PENDIDIKAN ISLAM DI INDONESIA DALAM PERSPEKTIF POLITIK - Restu Rahmawati (Pascasarjana IAIN Sorong, 2018)
In contrast of early nineteen century when the school prohibition for indigenous people was executed, the early century of twenty started up the educational chance. Though the education permitted only for the children of priyayi, rich men and plutocrat, also Dutch government functionary. The queen Wilhelmina‟s policy that politically determinates the discretion for the need of education came along with the time when Islamic education institution gradually founded and dispersed in Java and Sumatera. As it was influenced by colonial government stability, this article covers the education project of Dutch colonial government and institutional Islamic education, includes political Islamic education policy with its intention.